2018
DOI: 10.4081/gh.2018.645
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate spatiotemporal disease mapping of cancer of the breast and cervix uteri among Iranian women

Abstract: Cervical cancer in women is one of the most common cancers and breast cancer has grown dramatically in recent years. The purpose of this study was to map the incidence of breast and cervix uteri cancer among Iranian women over a 6-year period (2004-2009) searching for trend changes and risk factors. Cancer incidence data were extracted from the annual reports of the National Cancer Registry in Iran. Hierarchical Bayesian models, including random spatial and temporal effects was utilized together with bivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 34 publications
(32 reference statements)
1
35
0
Order By: Relevance
“…We found that two South-Eastern and Southern provinces, Sistan and Baluchistan and Hormozgan have lowest RR for both cancers. Northe and North-West part of country including Mazandaran, East-Azerbaijan, and Kurdistan are the highest risk areas regarding the two stomach and colorectal cancers and these obtained results are consistent with those of Mahaki et al ,[ 17 ] Kavousi et al ,[ 33 ] Rastaghi et al [ 34 ] and Nasrazadani et al [ 35 ]…”
Section: Discussionsupporting
confidence: 89%
“…We found that two South-Eastern and Southern provinces, Sistan and Baluchistan and Hormozgan have lowest RR for both cancers. Northe and North-West part of country including Mazandaran, East-Azerbaijan, and Kurdistan are the highest risk areas regarding the two stomach and colorectal cancers and these obtained results are consistent with those of Mahaki et al ,[ 17 ] Kavousi et al ,[ 33 ] Rastaghi et al [ 34 ] and Nasrazadani et al [ 35 ]…”
Section: Discussionsupporting
confidence: 89%
“…ε i 1 , ε i 92 , ε i 3 represent surrogate of specific components as surrogates of specific risk factors for these studied cancers. [ 13 14 15 ] To put it more simply, this model tries to estimate the relative risk of disease to recognize high risky regions, and decompose the risk of diseases to shared and specific effects. According to spatial distribution of shared and specific effects, we emphasize about possible risk factors.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, shared components (SC) model (4) was used for highlighting the similarity and non-similarity of spatial patterns of stomach, esophageal, and lung cancers mortality in the counties of Iran due to shared and specific risk factors. Such a model has been used in several studies for determining the spatial changes of risk factors in some diseases (7,14,15). In this case, counts of stomach, esophageal, and lung cancers mortality refer to the variables of the model response with a shared risk factor (smoking (16)(17)(18)) and the other risk factor, i.e.…”
Section: Introductionmentioning
confidence: 99%